Implementasi Teknologi dalam Pengenalan Ilmu Kebudayaan Tari Kebagh Sebagai Media Pembelajaran Kecerdasan Buatan Berbasis Web - Nurmaleni; Putra, Yendi; P, Etika Melsyah; Yulhan; Anwar, Edwin; Temat, leni (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The preservation of local culture requires learning media that keep pace with technological advancements, enabling the younger generation to engage with history and cultural values ​​in a more compelling and interactive manner. One such local cultural element is the Kebagh Dance, a cultural icon of the Besemah community in Pagar Alam City. This study aims to develop and implement a web-based learning medium utilizing artificial intelligence (AI) technology to introduce the history, music, folklore, and cultural aspects associated with the Kebagh Dance. The research methodology encompasses problem analysis, data collection, design, planning, development, testing, and implementation. Data were gathered through observation and user testing involving visitors to the Pagar Alam City Government Library, comprising both students and the general public. The learning medium was developed as a website featuring videos, images, audio, music, and AI-driven features to facilitate the interactive delivery of cultural information. Testing results revealed no errors in content delivery, while the media assessment achieved a score of 76%, placing it in the